Integrated reporting of environmental, social, and governance and financial data: Does the market value integrated reports? - Alexander Landau; Janina Rochell; Christian Klein; Bernhard Zwergel (Business Strategy and the Environment, 2020)
The concept of reporting nonfinancial information within the annual report, so-called Integrated Reporting (IR) is a rising topic in reporting practice. Supporters claim that IR provides a better view regarding the value creation of a firm.
Keywords: 330; assurance; ESG reporting; Integrated Reporting; Ohlson model; value-relevance